Technopreneurship and Digital Era in Global Regulation - Alias, Mohd Nasir; Shamsudin, Mohd Farid; Majid, Zawiah Abdul; Hakim, Mohd Nasrul (Prosiding Seminar; 2020: 2020 International Conference of Interdisciplinary SciencesDO - 10.32503/prosidingseminar.v2i1.20, 2020)
Some people may have overlooked the importance of technopreneurship and its development in the digital economy especially involving globalization of economic and commercial activities. While most people might have read and understand about entrepreneurship but new technologies have nurtured the rise of technopreneurs in order to sustain in the global competitiveness as well as to equip oneself with latest technological knowledge. Therefore, the author will emphasize the differences between entrepreneurship and technopreneurship in-addition related to this field of digital era in global regulation. The relationship between technopreneurhip and digital era will be explained and will focused on opportunities and challenges for better understanding.